The Kapitean Stage (Upper Miocene) of New Zealand - Kennett, James Peter (11658352) (1965)
The ten chapters in this thesis are presented in the form of nine independent papers and a note. A separate abstract is given below for each chapter. I. The type section of the Kapitean Stage and four other sections in north Westland were examined in detail. The stratigraphy of each section is described and the distribution of 300 species of Foraminifera and 38 species of Mollusca from the Upper Tongaporutuan and Kapitean is discussed. Neogene sediments, previously classed as "Blue Bottom" are separated into four formations. Six zones based on Foraminifera form an essentially continuous sequence ranging from Upper Miocene to Pliocene in age. Four zones based on Mollusca correspond to four of the foraminiferal zones. Depth of deposition for each formation is inferred from paleoecology and a geological history is inferred for the Upper Miocene and Pliocene in north Westland. The type Kapitean and the Kapitean throughout north Westland consists of relatively shallow-water facies. From this study it could not be correlated satisfactorily with deep-water facies elsewhere in New Zealand and its relationship to the Bolivinita compressa Zone could not be determined. The taxonomy of one hundred and five species of Foraminifera is discussed and seven species are described as new: Textularia barnwelli, Quinqueloculina waimea, Virgulina vellai, Florilus olsoni, Notorotalia macinnesi, Globorotalia conomiozea and Cibicides gibsoni. A gradational bioseries of Hofkeruva is described and the evolution and first occurrence of Globorotalia crassaformis (Galloway & Wissler) is discussed. II. About 350 ft. of Kapitean beds exposed in sea cliffs at Cape Foulwind, West Coast, are conformably overlain by Opoitian and Conformably underlain by Tongaporutuan. Seven foraminiferal samples were collected from a uniform and continuous section of marine siltstone. A lithological column and a foraminiferal range chart are presented. Paleoecology and stratigraphic paleontology are discussed. III. At Cape Foulwind specimens of Textularia kapitea Finlay from Six samples show a well defined evolutionary change with time. Two subspecies, one of early to middle Kapitean and one of late Kapitean to early Opoitian age, are established Textularia miozea appears to be the ancestor of T. kapitea. IV. Upper Miocene to Pliocene strata in north Westland and Marlborough contain abundant fossils representing a bioseries of planktonic Foraminifera showing gradual progressive morphological changes. The bioseries commenced with Globorotalia miozea Finlay and ended with Globorotalia crassformis (Galloway and Wissler). The form representing the intermediate stage of the bioseries at Marlborough, differs slightly from the corresponding form at north Westland, 150 miles to the south-west, but the end form is the same in both areas. V. In Marlborough, two stratigraphic sections ranging from Middle Tongaporutuan to Opoitian (Upper Miocene to Lower Pliocene) in age were examined. They lie only 5 miles apart, but one is predominantly deep-water facies and the other is predominantly shallow water facies. Ranges of Foraminifera and Mollusca are shown on charts and local foraminiferal and molluscan zones are established. By correlating key horizons in these sections it has been possible to determine relative stratigraphic ranges of important deep-water and shallow-water fossils, including key Foraminifera and the Kapitean key Mollusca. The base of the Kapitean Stage in the shallow-water section is marked by the first appearance of the key Kapitean Mollusca. The corresponding horizon in the deep-water section can be defined by an evolutionary stage of the Globorotalia crassaformis bioseries. The Kapitean Stage is shown to be relatively thin and to be equivalent to about the upper half of the Bolivinita compressa Zone that is found only in deep-water facies. Paleoecological changes indicate significant changes in depth of deposition in both sections and these depth changes were almost certainly synchronous. The sea was relatively shallow during the Kapitean Age. The biostratigraphic divisions are closely related to the changes in depth of deposition. VI. Six sections through the Upper Miocene and Lower Pliocene in Wairarapa and southern Hawkes Bay were examined in detail. Ranges of Foraminifera and Mollusca are given for each section and lithologies are shown on columnar sections. For the stratigraphic interval from Upper Tongaporutuan to Opoitian, two parallel sets of zones are recognized. One set of zones is based of Foraminifera and is applicable mainly to deep-water facies and the other is based on Mollusca and is applicable only to shallow-water facies. Diagnostic species for each zone are listed. In shallow-water facies the Kapitean Stage is determined mainly by the presence of Sectipecten wollastoni. In deep-water facies which lack the key Mollusca, it is determined by means of the Globorotalia crassaformis bioseries. The absence of the Kapitean in two of the sections is shown mainly by the absence of the characteristic Kapitean parts of the G. crassaformis bioseries and the Siphotextularia wairoana bioseries. The paleoecology throughout each section is described, and indicates that at most places the sea was relatively shallow during the Kapitean Age. VII. Four eastern North Island sections through the Upper Miocene and Lower Pliocene were examined: at Maraetotara River, central Hawkes Bay; at Ruakituri River, northern Hawkes Bay; at Waimata river, Gisborne; and near Te Araroa, East Cape. Distribution of Foraminifera is shown on charts, and lithologies are shown on columnar sections. Four well defined biostratigraphic units can be recognised for the Foraminifera, from oldest to youngest; Pohana Zone, Compressa Zone, Conomiozea Zone, and Crassaformis Zone. Diagnostic Species are listed for each of these zones. In one section the Kapitean Stage is represented by shallow-water facies and is marked by the key Kapitean Mollusca. In two sections it is represented by deep-water facies and is determined by means of the Globorotalia crassaformis bioseries. In the fourth section, the absence of uppermost Upper Tongaporutuan, Kapitean and basal Opoitian is shown by the absence of part of the G. crassaformis bioseries. The paleoecology throughout each section is described, and indicates that the sea shallowed near the end of the Tongaporutuan Age, remained shallow during the Kapitean Age and deepened again at the beginning of the Opoitian Age. VIII. The stratigraphic ranges in inland Taranaki are given for some important Foraminifera relative to those of the Mollusca Sectipecten grangei and S. wollastoni. IX. The following fourteen new species of fossil Foraminifera are described and illustrated from the Upper Miocene and Lower Pliocene of New Zealand: Textularia crater, Siphotextularia dawesi, Ruakituria pseudorobusta, Karreriella fasigatus, Arenodosaria turris, Vaginulinopsis carinata, Bolivinita finlayi, Brizalina srinivasani, Kolesnikovella zealandica, Discorbinella hamasuturalis, Notorotalia mammiligera, Cibicides porrodeliquatus, Cibicides teararus and Pleurostomella parviapertura. Known stratigrahic ranges and inferred depth ranges are given for each species. The new genus Ruakituria (Ataxophragmiidae) is erected for the species formerly know as Dorothia robusta Keyzer. X. The salient features of New Zealand Upper Miocene and Lower Pliocene microfaunas are outlined, and criteria for recognising the Kapitean Stage are summarized. Paleoecology suggests that he Kapitean Stage represents an interval of time when seas were relatively shallow, that the shallowing took place in the latest part of the Tongaporutuan Age and that deepening took place in the earliest part of the Opoitian Age. The changes in depth of sea caused many temporary "facies" changes in fossil faunas at any particular places, but the Kapitean Stage is soundly based on a few permanent changes of both macrofauna and microfauna. The Kapitean Stage is represented by fairly shallow-water facies at many places but by fairly deep-water facies at other places. Shallow-water and deep-water facies contain very few age diagnostic fossils in common, but can be correlated by means of the Globorotalia crassaformis bioseries, a sequence of planktonic Foraminifera showing gradual progressive morphological change. In nearly all sections the Kapitean Stage is thin compared with the overlying Opoitian and underlying Upper Tongaporutuan, and this is attributed to a decreased rate of deposition due to shallowing and increased by-passing of sediment. Kapitean microfaunas show a slight but distinct change from north to south, this being attributed to latitudinal temperature difference. The previously suggested correlation of the Kapitean Stage with the Pontian Stage of Europe is probably correct. The shallow seas during the Kapitean Age in New Zealand appear to have coincided with a phase of regression in Europe and in other parts of the world and may have a eustatic rather than a tectonic cause.